2008
DOI: 10.1038/npp.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

The Ventral Pallidum is Critically Involved in the Development and Expression of Morphine-Induced Sensitization

Abstract: Repeated, intermittent exposure to drugs of abuse results in response enhancements to subsequent drug treatments, a phenomenon referred to as sensitization. As persistent neuronal sensitization may contribute to the long-lasting consequences of drug abuse, characterizing the neuroanatomical substrates of sensitization is providing insights into addiction. It is known that the ventral tegmental area (VTA) is necessary for induction, and expression involves the nucleus accumbens (NAc). We reveal here that the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…To our knowledge, this latter finding is original because only 2 studies already showed reversal of EIBS, but with a nonpharmacological approach (Fallopa et al, 2012;Rueda et al, 2012). Altogether, these data suggest that NaB prevented or reversed neuroadaptations underlying EIBS, despite the fact that these neuroadaptations may be distinct between both induction and expression phases (Mickiewicz et al, 2009). Conversely, because NaB has no effect on 2.0 g/kg-EIBS induction or expression, we hypothesized that these apparent disparate findings may result from profound dissimilar neuroadaptations induced by both EtOH doses.…”
Section: Blockade and Reversal Of Eibs By Nabmentioning
confidence: 56%
See 1 more Smart Citation
“…To our knowledge, this latter finding is original because only 2 studies already showed reversal of EIBS, but with a nonpharmacological approach (Fallopa et al, 2012;Rueda et al, 2012). Altogether, these data suggest that NaB prevented or reversed neuroadaptations underlying EIBS, despite the fact that these neuroadaptations may be distinct between both induction and expression phases (Mickiewicz et al, 2009). Conversely, because NaB has no effect on 2.0 g/kg-EIBS induction or expression, we hypothesized that these apparent disparate findings may result from profound dissimilar neuroadaptations induced by both EtOH doses.…”
Section: Blockade and Reversal Of Eibs By Nabmentioning
confidence: 56%
“…Different studies suggest that the 2 phases may involve distinct brain structures. The ventral tegmental area may be involved in the induction, while the nucleus accumbens may be more involved in the expression (Mickiewicz et al, 2009).…”
mentioning
confidence: 99%
“…S3 c and d). Morphine has been shown to elicit enhanced locomotor-activating effects (behavioral sensitization) with repeated, intermittent administrations (22,23). Indeed, A/A animals showed behavioral sensitization following repeated morphine injections, while G/G animals did not (day Ï« genotype Ï« treatment interaction, F 6,138 Ï­ 9.688, P Ïœ 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Ibotenate lesions of the amygdala have been reported to either block or have no effect on the development of amphetamine sensitization (Wolf et al, 1995;Cador et al, 1999). Finally, studies with -opioid agonists and antagonists suggest that ventral palladium is involved in both the initiation and expression of behavioral sensitization to morphine (Mickiewicz et al, 2009). As will be discussed further below, it is likely that each of these brain regions affects the development of sensitization by influencing the mesocorticolimbic dopamine system.…”
Section: B Sensitizationmentioning
confidence: 99%